Comportamiento reproductivo, forrajeo y uso de hábitat de Coccyzus ferrugineus (Cuculiformes: Cuculidae) en la Isla del Coco, Costa Ric - Tenorio, Javier (2020)
Introducción: Coccyzus ferrugineus is the least studied endemic bird of Isla del Coco, many aspects of its natural history and behavior remain unknown, being one the least known species in Costa Rica. Objective: To describe the reproductive behavior, foraging and habitat use of C. ferrugineus to generate information for making conservation decisions for the species. Methods: Direct behavioral observations (foraging, courtship, vocalization, feeding and intercourse) were made in plots between 0-400 m above sea level, during two observation periods (morning and afternoon). A description of the foraging behavior and the reproductive cycle is presented. Results: C. ferrugineus uses the entire altitudinal gradient of the island to reproduce, from sea level to 400 m altitude in the cloud forest. Its reproductive season is marked by the beginning of the dry season. No significant differences were found between the established behavior categories and the time of day (Fisher, P> 0.05). However, significant differences were shown for the behavioral categories and the vertical stratum (Fisher, P <0.05) demonstrating that it uses the entire vertical stratum of the vegetation structure. Conclusions: This study represents the basis for the knowledge of the reproductive biology and natural history of C. ferrugineus, it is urgent to carry out more studies on this species to be able to protect it and conserve the terrestrial ecosystem of Isla del Coco.